2001
DOI: 10.1007/s001340101025
|View full text |Cite
|
Sign up to set email alerts
|

Release of interleukin-10 by reinfusion of salvaged blood after knee arthroplasty

Abstract: Total knee arthroplasty results in the release of interleukin-10. Transfusion of filtered salvaged blood leads to higher levels of cytokines IL-6 and IL-10 than after transfusion of washed and centrifuged salvaged blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 7 publications
0
14
2
Order By: Relevance
“…Previous reports were either multi-centre studies of patients following diverse incidents of trauma [11] or studies using alternative blood collection procedures [26][27][28][33][34][35]. Major features of PTI included subnormal levels of the proinflammatory cytokines IL-1β, IL-2, IL-17A, IFN-γ and TNF-α, a picture that was reversed dramatically by salvaged blood.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports were either multi-centre studies of patients following diverse incidents of trauma [11] or studies using alternative blood collection procedures [26][27][28][33][34][35]. Major features of PTI included subnormal levels of the proinflammatory cytokines IL-1β, IL-2, IL-17A, IFN-γ and TNF-α, a picture that was reversed dramatically by salvaged blood.…”
Section: Discussionmentioning
confidence: 99%
“…(Huët et al 1999, Tylman et al 2001, Jones et al 2004, Carless et al 2010, Tsumara et al 2006, Smith et al 2007, Zacharopoulos et al 2007, Amin et al 2008, Tripkovic et al 2008, Munoz et al 2011. The haematocrit of drain-blood is approximately 0.25-0.30 l/l due to mixture with chyle.…”
Section: Autotransfusion In Orthopaedic Surgerymentioning
confidence: 99%
“…The different baseline characteristics of the subjects, especially the presence of malignancy, may have affected the results. Previous investigations have demonstrated that preoperative values of the infl ammatory cytokines that we investigated were similar in patients undergoing either surgery for cancer removal or orthopedic reconstructive surgery [4,11,12,27]. However, it is still possible that the transfusion-related infl ammatory response was actually less in our ANH group, but the difference may have been undetected due to the infl uence of a more stressful surgical procedure in the ANH group.…”
Section: Discussionmentioning
confidence: 50%
“…Heiss et al [11] reported a significant increase in plasma IL-10 after an allogeneic transfusion but not after an autologous transfusion in patients undergoing colorectal cancer surgery. Tylman et al [27] reported that reinfusion of salvaged blood resulted in an increased plasma IL-10 concentration. These results suggest that the difference between PD and ANH had less of an impact on the transfusion-triggered infl ammatory response compared to allogeneic transfusion or the reinfusion of salvaged blood.…”
Section: Discussionmentioning
confidence: 98%